TEKNOLOGI PENGOLAHAN AIR SIAP MINUM UNTUK DAERAH PADAT PENDUDUK - Widayat, Wahyu (Center for Environmental Technology, 2005)
One of common problem on dense settlement area in Indonesia is the need for clean water and especially at rural and isolated areas this problem have not been properly solved yet. The ground and river water which consume by the community do not meet the requirement for drinking water, even at several places the water is not suitable to drink. The standard requirement for drinking water have to comply with the physical, chemical and biological requirements and if one parameter do not comply with the requirement then the water is not proper to drink.Most of residential area in Indonesia have poor water quality and have not got clean water services from local PAM, therefore in order to fulfill the need for drinking water, the community buy bottled drinking water which is very expensive.To overcome the above problem, a pilotÃ‚Â unit package of technology have been developed, to treat well water or clean water from PAM to be direct to drink water ( no need to boiled it ). The unit consists of water pump, sand filter, mangan zeolit filter, activated carbon filter, cartridge filter, ultra violet sterilisator and ozon generatorÃ‚Â Kata Kunci : Air tanah, air PAM, pengolahan air,Ã‚Â air siap minum